Pengaruh Green Product, Servicescape dan Kualitas Layanan terhadap Kepuasan Konsumen pada Resto Berbasis Alam - Richardus Bowo Harcahyo; Sentot Suciarto Athanasius; Veronica Kusdiartini (Universitas Katolik Soegijapranata, Semarang, 2021)
Restaurant consumers will choose and visit a restaurant if they are satisfied, well served and get what they need at the restaurant. The problem of this research is how the influence of service quality, green product and servicescape on consumer satisfaction. The purpose of this study was to determine the effect of green product, servicescape and service quality on consumer satisfaction at the Surrounding Nature-Based Restaurant. The restaurant's efforts in maintaining customer satisfaction are inseparable from the quality of service provided by the restaurant. In addition, consumers who visit restaurants not only enjoy culinary delights, but also enjoy the servicescape or the natural scenery around the restaurant. Kampoeng Rawa restaurant in Ambarawa is a restaurant in the middle of a stretch of rice fields and just into the middle of Rawapening swamp area and is above the water. The view in the middle of the swamp and water makes the restaurant atmosphere attractive for visitors. This research was a consumer survey of Kampoeng Rawa restaurant visitors who enjoy culinary and the nature around the restaurant. Based on quota accidental sampling, 60 consumer respondents were determined who dine in at the Kampoeng Rawa restaurant during March 2021. The results showed that there was a positive and significant effect of service quality and servicescape variables on restaurant customer satisfaction. Green products do not have a significant effect. Furthermore, sustainable restaurant service management will have an impact on its contribution to the economy of private owners, BUMDES owners and the surrounding community who are employees. A restaurant that is managed by paying attention to the quality of service and an attractive surrounding atmosphere can lead to satisfaction for restaurant consumers.